Responsabilidade social: atuação da unidade móvel de biblioteca do SESC-TO - Bibliosesc - Paz, Maria Damiana Melo da (Universidade Federal do Tocantins, 2024)
The purpose of this paper is to discuss the importance of the work carried out by the mobile library unit of SESC / TO in Palmas and how it can help and encourage the reading of young people and children who are not in the habit of reading. For this it was necessary to analyze what the BiblioSesc project is and how the work is developed. In this way, the BiblioSesc Project has achieved its goal of training readers and promoting the improvement of the quality of life through access to information, since it is a free, free and open source library. As for nature, the research had a quantitative-qualitative approach of exploratory nature. A questionnaire with closed and open questions was used as a data collection instrument to identify the user's profile and the contribution of the project to the users' reading practice. The analysis of the data showed that the users are stimulated as to the reading practice in the project, since they do not have access to the other library, and consequently access to the information. Therefore, it was verified that the project's performance in the communities in partnership with the associations, has contributed to the social inclusion of the users of BiblioSesc.